(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
In recent years, business has gotten increasingly difficult, and a globalised market requires comprehensive Accounting Standards that can be applied equally and promote fairness across corporations and regions. In the age of globalisation, India needs and wants Ind AS. With the introduction of IFRS globally, there was an urgent need to have similar standards for India as well. Therefore, Ind AS were converged with IFRS in 2011. Ind AS were made applicable in India from April 2015 voluntarily and then in a phased manner it was made mandatory from April 2016. The present study focusses on finding the factors affecting the perception of Chartered Accountants in India regarding the adoption of Ind AS. Primary data was collected on structured Likert scale questionnaire and data was analysed using Smart PLS 4. The findings of the study revealed that challenges and limitation have a negative impact on the perception while utilities, training and development of common understanding have a positive impact. Adoption process was found to be insignificant.